Un estudio comparativo de la circulación de las producciones artísticas Iskonawa y Shipibo-Konibo - Hernández Ronchi, Hillary (2022)
Taking into account Appadurai’s proposal on the social life of things and regimes of value (1991), the following article analyzes the circulation of some artistic pieces of the Iskonawa and Shipibo-Konibo indigenous peoples in new circuits and spaces of value. Likewise, Alfred Gell’s proposal on art as a system of action is used to reflect on the social effects that these objects of art produce on the intermediaries and their social environment. Initially, the case of the artistic production of the Iskonawa women of the ‘Asociación de artesanas Pari Awin’ is worked, followed by the artistic production of the Shipibo-Konibo. For this purpose, it has been chosen to present a comparative study between both of these productions, with a focus on the aesthetics and their insertion into contemporary markets such as galleries, fairs, among others. The way in which certain objects are inserted in specific spaces and how others do not attain the same exposure is analyzed. This takes into account the relationship between both indigenous peoples, as some of the Iskonawa artists have a previous history with the production of Shipibo-konibo designs, due to the cultural exchange generated by their coexistence on the same territory.